Analisis Efektivitas Motion graphic Sebagai Media Informasi Company profile Polibatam Press Menggunakan Epic Model - Supardianto, Supardianto; Octaviany, Wanda Dwi (JURNAL INTEGRASI, 2023)
Polibatam Press, a business unit under the Batam State Polytechnic, which was founded in 2017, focuses on publishing books and scientific works. Even though it currently uses a website for publishing and social media for promotion, Polibatam Press does not yet have a company profile that can be easily distributed via various social media platforms. This research aims to develop a company profile video in the form of motion graphics to improve Polibatam Press branding. In the design process, the Villamil-Molina method was used, and its effectiveness was analyzed using the EPIC model. The research results showed that alpha testing was 4.23, which means "feasible,", and beta testing resulted in an EPIC rate of 3.92, which was interpreted as "effective." Based on these results, the resulting motion graphic video fulfills the purpose of its creation by being able to provide information effectively to the people who watch it